Management of Islamic Bank Services - DJafar; Agus Umar Ghazali; Harun Abdullah; Sugeng Sapta Aji; Muhammad Akbardin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Islamic banking is a financial institution that tries to find solutions to people's financial problems, but has its own challenges in society. This is because the public's interest in Islamic banking is no different from conventional banking. It is interesting to be a community partner as a place for transactions. In this study, the authors used a descriptive research method in the form of a library research (library research) to discuss the service model of Islamic banking services. The results of the study show that Islamic banking services are different from conventional banking, although the products are almost the same as savings, current accounts and time deposits which differ in the type of contract, namely mudharabah, musyarakah, murabaha, etc. all transactions are based on sharia principles, namely principles that promote togetherness and mutual assistance to achieve mutual benefit that are oriented not only to the world but also to the ukhrawi.